2006
DOI: 10.1659/0276-4741(2006)26[124:tiohea]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Household Economics and Farming Aspects on Adoption of Traditional Agroforestry in Western Himalaya

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The impact of gender on adoption of agroforestry is best demonstrated by the fact that some communities restrict land ownership and tree-based investment and exploitation to men (Kiptot and Franzel, 2011;Assé and Lassoie, 2011). For household size, it has been observed that large households have sufficient household labour which can be allocated to intensive tree planting and management while small households with less labour are more likely to adopt less intensive practices (Sebastian et al 2014;Mukungei et al 2013;Sood, 2006). Since the households in the study area had similar biophysical conditions, we assume that socioeconomic factors play a fundamental role in household choice of agroforestry adoption and a particular management system.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of gender on adoption of agroforestry is best demonstrated by the fact that some communities restrict land ownership and tree-based investment and exploitation to men (Kiptot and Franzel, 2011;Assé and Lassoie, 2011). For household size, it has been observed that large households have sufficient household labour which can be allocated to intensive tree planting and management while small households with less labour are more likely to adopt less intensive practices (Sebastian et al 2014;Mukungei et al 2013;Sood, 2006). Since the households in the study area had similar biophysical conditions, we assume that socioeconomic factors play a fundamental role in household choice of agroforestry adoption and a particular management system.…”
Section: Hypothesesmentioning
confidence: 99%
“…According to Mukungei et al (2013), household composition dictates how responsibilities are allocated to different family members. Sood (2006) also reported greater adoption of agroforestry practices through planting by households with enough labor, while households with less labor opted for less labor intensive practices like FMNR. Sood (2006) also reported greater adoption of agroforestry practices through planting by households with enough labor, while households with less labor opted for less labor intensive practices like FMNR.…”
Section: Socioeconomic Factors Affecting Tree Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and natural resource management (Ong and Kho ), increase yields (Bayalaa et al. ), income (Sood ), and thus strengthen food security (Sanchez et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that models that integrate woody perennials (trees, shrubs, palms, bamboos, etc. ) with crops and/or animals can contribute to climate change adaptation (Lin et al 2008) and mitigation (Budiadi and Ishii 2010), improve soils (Glover et al 2012) and natural resource management (Ong and Kho 2015), increase yields (Bayalaa et al 2012), income (Sood 2006), and thus strengthen food security (Sanchez et al 1997). Furthermore, such systems allow for food, feed, and several types of bioenergy to be produced respecting economic, social, and environmental sustainability indicators.…”
Section: Introductionmentioning
confidence: 99%